Impedance spectroscopy characterization of GaAs nanowire bundles grown by metal-catalyzed molecular beam epitaxy - Tirado, Monica Cecilia (2010)
Vertically aligned GaAs nanowire (NW) bundles grown by gas-source molecular beam epitaxy on an n-doped GaAs substrate by a metal catalysis method and embedded in an insulating matrix (SU8-2) were studied by impedance spectroscopy. The DC current-voltage characteristics measured between Au dot contacts to the NW tips and the substrate exhibited Schottky behavior. A detailed analysis of the impedance data measured in reverse bias conditions is presented, which enables the elimination of the stray capacitance due to the insulating matrix, and the separation of the different contributions to the total admittance from the metal/NW Schottky interface and from the NW region beyond the barrier region. The observed NW conductances and capacitances are shown to be consistent with rough estimates based on the GaAs conductivity and permittivity data and the NW dimensions, and the NW conductance increases as a power law of the frequency. Possible charge transport mechanisms to explain this result are discussed.